Between cooperation and individual action: Relational capital of Poland’s local government - Nowakowska, Aleksandra; Kusideł, Ewa; Michalak, Magdalena (Quaestiones Geographicae, 2025)
Relational capital is a commonly used concept in spatial economics, yet it remains poorly researched, particularly within the context of territorial development. This article aims to innovate, operationalise and quantify the relational capital of local government units. It allows for the analysis of intensity and spatial differences in relational capital, creates a ranking of local governments and evaluates external and internal cooperation relations. It considers four dimensions of relations: international cooperation between twin cities, membership in national and international local government organisations, inter-municipal cooperation and cooperation with NGOs. Questionnaire surveys carried out in local government units were used as a principal research method, which provided the basis for the development of the synthetic measure of relational capital intensity. The research revealed a low level of local government relational capital in Poland and its spatial heterogeneity across all dimensions of relations. It showed a clear domination of internal cooperation relations over external ones.